Political podcasts in Brazil: left-leaning shows in a polarized market - Gambaro, Daniel (AoIR Selected Papers of Internet Research, 2026)
This study examines the Brazilian podcast market to understand how the subject of "politics" circulates on streaming platforms. Specifically, it will show how certain programs lean toward the left or the right end of the political spectrum and, furthermore, it will describe how left-wing agents organize within this market. This is a relevant discussion since political polarization in Brazil has intensified during the last decade, materialized on disputes around a legitimate ‘vision of Brazil’ to define the future of the country – i.e., around values of equality or dispositions of conservative-liberal ideologies. By means of a technographic analysis of four streaming services (their recommendations through lists and through search results), a corpus of analysis of 511 programmes has been set. The results showed that the services prioritize economic rather than political criteria, returning more recommendations that originate from traditional media. Moreover, left-leaning podcasts quantitatively more suggested than right-leaning, but, in terms of audience reach, the recommended right-leaning podcasts tend to gather greater numbers. Thus, right-wing media outlets and influencers seem to organize more effectively to explore the podcast market, while left-wing individuals and institutions diversify across numerous channels that often struggle to maintain continuity.